PERJUANGAN TOKOH UTAMA NOVEL INSYA ALLAH AKU BISA SEKOLAH (DUL ABDUL RAHMAN) KAJIAN PSIKOLOGI SASTRA & NILAI PENDIDIKAN - Achmad Yuhdi (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2019)
ABSTRACT Novel Insya Allah Aku Bisa Sekolah is a novel that has a myriad of inspiration that we can get. Inspiration in the novel became the topic of our research. One of them, a picture of a fishermans child who wants to be highly educated, but has no cost because of the situation of parents who are only as fishermen illustrated from the main character in the novel. This study aims to explain the struggle of the main character, the study of psychological psychology, and the educational value contained in the novel. To perfect our research, the methods we use must be precise, one of them is a qualitative method with descriptive design support. While the source of the data source that we use  in our research is novel Insya Allah Aku Bisa Sekolah. The results of our research found in terms of the struggles of the main characters who always struggle, the study of literary psychology that the struggle of the main characters who are not desperate, and the novel contains educational values: Moral education values, social education values, and cultural education values.Key Word: Novels, Inspiration, Main Characters, The Study of Psychological Psychology,       and Educational Values.